NowHere : Space, Time and Modernity - A. F., Robertson; A. F., Robertson; Adam B., Seligman; Adam B., Seligman; Allan G., Grapard; Allan G., Grapard; Ann, Bermingham; Ann, Bermingham; Anthony, Giddens; Anthony, Giddens; Boden, Deirdre; Carol Brooks, Gardner; et al. (University of California Press, 2020)
The fall of the Berlin wall, the uprising at Tiananmen Square, the war in the Persian Gulf, the conflict in Bosnia--such events have been fundamentally affected by modern technology. As we become instant spectators of war, famine, and revolution, time and space assume new global meanings. This provocative volume presents an eclectic group of contributors who attempt to make sense of the "now" and the "here" that define the modern age. The essays, by anthropologists, religionists, geographers, linguists, sociologists, and historians, explore the temporal and spatial facets of social life. Their range is remarkable and includes English landscape painting, talk in corporations, agoraphobic women, the ecological structure of Los Angeles, the cosmology of the Holocaust, and the ritual spaces of Buddhist Japan and the Church of the Holy Sepulchre in Jerusalem. The editors' introduction addresses the diversity of these empirical concerns and positions them within a rapidly expanding theoretical landscape. David Hockney's striking painting on the book jacket captures the tension between somewhere and everywhere, between space and place, now and just a moment ago--hence "nowhere" or "now/here.".